Understanding Domestic Violence Among Older Women in Ukraine: A Secondary Analysis Using Gender-Based Violence Screening Data - Rushwan, Sara (Journal of interpersonal violence, 2024)
This secondary descriptive analysis sought to understand Gender-Based Violence (GBV), with a focus on Domestic Violence (DV), among older women in Ukraine’s conflict setting. Analysis was conducted on a subsample of 150 women aged 60+ from GBV-Information Management System intake data of 12,480 GBV survivors. Fisher’s exact tests were used to compare differences in GBV incidents among women who experienced DV compared to other types of GBV. Using United Nations humanitarian and aging frameworks, qualitative analysis was completed following two rounds of coding. Sixty percent of women aged ≥60 experienced DV. Local women were more likely to experience DV versus displaced women (85.6% vs. 48.3%, p < .001). Six core themes emerged: experiencing versus witnessing violence, intergenerational conflict, livelihoods, alcohol, humiliation, and neglect. Deeper understanding of DV among older women in humanitarian settings is needed, strengthening a call to action to prioritize protection against, and prevention of, GBV more broadly among this marginalized group.